Unpacking digital ID systems' early policy process - David Eaves; Beatriz Vasconcellos; Matthew McNaughton; Giulia Lanzuolo (Technology and Regulation)
The past decade has seen a growth in interest in the governance of digital public infrastructures (DPI) - and digital identities in particular - as these systems are increasingly deployed to improve social and economic outcomes at scale. This paper analyzes the case of Jamaica's National ID's early policy process. It unveils and unpacks the complexity embedded in the political, legal, and administrative dimensions of the digital ID policy design and legislative processes. It argues that inherent tensions and tradeoffs emerge and dynamically evolve during the policy process. We conceptualize and analyze four in the Jamaican context. The lessons on the Jamaica case aim to contribute with policy insights for legislators and policymakers on running more accountable, just, and inclusive ID systems' design processes.